Divestments by MNEs: What do we know about why they happen? - Maria Borga; Monika Sztajerowska (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Divestments are a frequent yet understudied corporate phenomenon. The authors outline key findings on the drivers of divestment by multinational enterprises using a large firm-level dataset and call for further research and a more explicit focus on divestments in data collection and policy-making.
Keywords: 330